Low-Intensity Focused Ultrasound Stimulation Ameliorates Working Memory Dysfunctions in Vascular Dementia Rats via Improving Neuronal Environment - Wang, Faqi; Wang, Qian; Wang, Ling; Ren, Jing; Song, Xizi; Tian, Yutao; Zheng, Chenguang; Yang, Jiajia; Ming, Dong (Frontiers in Aging Neuroscience, 2022)
In recent years, low intensity focused ultrasound stimulation (LIFUS), as a novel non-invasive brain stimulation technology, has been considered as a promising technique for neuromodulation and treating neurological diseases. It has been found that LIFUS shows remarkable neuroprotective effects on some neurological disorders such as depression, Alzheimer’s disease and vascular dementia (VD). Although LIFUS has shown neuroprotective effects on VD rodents model, whether it could ameliorate VD-induced working memory impairment is still not clarified. Therefore, the purpose of this study was to address this issue and the underlying mechanism. The VD model was established on adult male Wistar rats via the bilateral common carotid artery occlusion and the LIFUS (center frequency = 0.5 MHz; Ispta = 500 mW/cm2, 10 mins/day) was applied targeting on bilateral medial prefrontal cortex (mPFC) for 2 weeks since 2 weeks after surgery. The main results showed that the LIFUS could significantly improve the performance of VD rats in the specific working memory tasks, including the delayed nonmatch-to-sample task and step-down task which might be associated with the improved synaptic functions in VD after LIFUS treatment. And we also found the improvement of the cerebral blood flow in LIFUS treatment rats. The underlying molecular mechanisms are associated with reducing neuroinflammation, such as inhibition of the TLR4/ NF-κB pathway and the decrease of pro-inflammatory cytokines. The amelioration of cerebral blood flow and neuroinflammation indicated that the living environment of the neurons in VD was improved after treatment of LIFUS. Taken together, our results suggest that the LIFUS targeted the bilateral mPFC can effectively and safely ameliorate reward-based spatial working memory and fear working memory dysfunctions induced by VD via restoring the living environment, survivability and synaptic functions of the neurons in mPFC of VD rats. Our findings indicate that LIFUS could be a promising and noninvasive treatment strategy for the clinical treatment of VD in the future.